2021
DOI: 10.3390/ijms222011159
|View full text |Cite
|
Sign up to set email alerts
|

An Open Question: Is Non-Ionizing Radiation a Tool for Controlling Apoptosis-Induced Proliferation?

Abstract: Non-ionizing radiation is commonly used in the clinical setting, despite its known ability to trigger oxidative stress and apoptosis, which can lead to damage and cell death. Although induction of cell death is typically considered harmful, apoptosis can also be beneficial in the right context. For example, cell death can serve as the signal for new tissue growth, such as in apoptosis-induced proliferation. Recent data has shown that exposure to non-ionizing radiation (such as weak static magnetic fields, weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Notably, a small production of ROS can lead to an increase in cell proliferation while an excess of them would lead to cell damage and reduced proliferation [ 44 , 45 ]. ROS production in turn can act as a potent regulator of MAPKs signaling cascade [ 46 , 47 ]. A low intensity and/or short-term exposure to ELF-MF may lead to a slight increase in ROS levels that constitute a cellular proliferative stimulus if are mantained in a physiological range (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, a small production of ROS can lead to an increase in cell proliferation while an excess of them would lead to cell damage and reduced proliferation [ 44 , 45 ]. ROS production in turn can act as a potent regulator of MAPKs signaling cascade [ 46 , 47 ]. A low intensity and/or short-term exposure to ELF-MF may lead to a slight increase in ROS levels that constitute a cellular proliferative stimulus if are mantained in a physiological range (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A low intensity and/or short-term exposure to ELF-MF may lead to a slight increase in ROS levels that constitute a cellular proliferative stimulus if are mantained in a physiological range (e.g. they are counteracted by the cellular antioxidant systems) [ 46 ]. Conversely, a higher increase in ROS associated with higher ELF-MF intensity and longer exposure time may lead to a ROS ammount that if it exceeds a critical threshold the cellular oxidative damage prevails decreasing cellular proliferation [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data demonstrate that many diverse cell types are responsive to MFs in physiologically meaningful ways. Thus, subatomic control of apoptosis and apoptosis-induced proliferation through quantum effects has been proposed as an exciting new avenue of therapeutic research (Hack et al, 2021). Likely the strongest benefit of this approach is the potential to tune applications of MFs to use some field strengths to remove unwanted cells and different field strengths to increase proliferation in regenerative or growth promoting settings.…”
Section: Quantum Effects On Cell Deathmentioning
confidence: 99%
“…Singlet state allows for recombination which yields reduced ROS levels. On the other hand, triplet state allows for diffusion of radicals which yields increased ROS levels 28 . It has been shown that, in principle, applied weak magnetic fields can raise the yield of free radicals and abolish recombination between 10 and 40% 29 .…”
Section: Introductionmentioning
confidence: 99%